Título Padrão - Alves, Maria lvone Mota; Tomé, Geraldo de Sousa (Arquivos de Ciências do Mar, 2018)
In this paper a comparative description is made of the macro and micro morphology of the pyloric caeca of the king mackerel, Scomberomorus cavalla ( Cuvier), and the Spanish mackerel, Scomberomorus maculatus (Mitchill). Enzime tests were also effected trying to determine its probable function.